Motivation for Learning Spanish as a Foreign Language: The Case of Chinese L1 Speakers at University Level - Lu, Xiuchuan; Zheng, Yongyan; Ren, Wei (Círculo de Lingüística Aplicada a la Comunicación, 2019)
The study of motivation based on non-English languages has attracted increasing attention in recent years, but related research in China is still limited. In an attempt to address this situation and with Dörnyei’s L2 Motivational Self System (L2MSS) as a framework, this paper studied seventeen Chinese university students’ motivational disposition to learn Spanish as their university major without abandoning their English study. Based on Q-methodology and complementary interviews, the results of our experiment showed that these Chinese students displayed two types of foreign-language learning motivation, one being “Multilingual group with an English orientation”, and the other “Strong Spanish”. The first group, profoundly influenced by their ideal L2 selves, had a strong motivation to learn English instead of Spanish, while the second group learned Spanish with a motivation closely related to their ought-to L2 selves. A variety of analyses were applied to answer questions pertaining to group differences and students’ attitudes towards Spanish and English learning mediated by individual, educational, and social factors.